2008
DOI: 10.1007/s12072-008-9115-9
|View full text |Cite
|
Sign up to set email alerts
|

A low steady HBsAg seroprevalence is associated with a low incidence of HBV-related liver cirrhosis and hepatocellular carcinoma in Mexico: a systematic review

Abstract: To address the relationship between hepatitis B virus (HBV) endemicity and HBV-related liver diseases in Mexico. Research literature reporting on HBsAg and antibody to hepatitis B core antigen (anti-HBc) prevalence in Mexican study groups were searched in NLM Gateway, PubMed, IMBIOMED, and others. Weighted mean prevalence (WMP) was calculated from the results of each study group. A total of 50 studies were analyzed. Three nationwide surveys revealed an HBsAg seroprevalence of less than 0.3%. Horizontal transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 56 publications
3
48
0
4
Order By: Relevance
“…HBV transmission may be due to exposure to biological fluids, e.g., unprotected sex practices. 33 Being sexually active showed a trend but not a statistically significant difference in its association with anti-HBc positive OR D 6.05; p D 0.208. This may be explained because the mean age in our study was 20 y and a positive correlation between age and detection of anti-HBc has been reported that it is doubled starting at 25 y in Mexico.…”
Section: Discussionmentioning
confidence: 87%
“…HBV transmission may be due to exposure to biological fluids, e.g., unprotected sex practices. 33 Being sexually active showed a trend but not a statistically significant difference in its association with anti-HBc positive OR D 6.05; p D 0.208. This may be explained because the mean age in our study was 20 y and a positive correlation between age and detection of anti-HBc has been reported that it is doubled starting at 25 y in Mexico.…”
Section: Discussionmentioning
confidence: 87%
“…As reported by others (Martin et al 2009), a low detection rate of certain cytokines, including IL-1, IL-6, IL-7, TNF-β, MIG, GMCSF and GCSF, was also observed in our study. However, even with a reduced percentage of samples testing positive for HBV DNA as a result of the low HBV prevalence in Mexico (Roman et al 2009), distinct cytokine profiles were seen in OHBinfected patients when compared to healthy individuals and patients that had resolved HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy restricts the bias that may impose the heterogeneous nature of the reports, and has proven to be valid when combining a number of studies with inherent heterogeneity in sample size and effects [67]. …”
Section: Methodsmentioning
confidence: 99%